1997
DOI: 10.1074/jbc.272.13.8744
|View full text |Cite
|
Sign up to set email alerts
|

The COOH-terminal Peptide Binding Domain Is Essential for Self-association of the Molecular Chaperone HSC70

Abstract: We have previously shown that the molecular chaperone HSC70 self-associates in solution into dimers, trimers, and probably high order oligomers, according to a slow temperature-and concentration-dependent equilibrium that is shifted toward the monomer upon binding of ATP peptides or unfolded proteins. To determine the structural basis of HSC70 self-association, the oligomerization properties of the isolated amino-and carboxyl-terminal domains of this protein have been analyzed by gel electrophoresis, size excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 52 publications
6
57
0
Order By: Relevance
“…The 22-kDa species seemed to be a degraded product of the 24-kDa hHsp70 520-641. These findings confirmed the results of the previous study (19) demonstrating that the dimerization as well as the oligomerization of Hsp70 was mediated through the C-terminal client-binding domain. Moreover, the results in Fig.…”
Section: Dimerization Of the C-terminal Client-binding Domain -Polyacsupporting
confidence: 82%
See 2 more Smart Citations
“…The 22-kDa species seemed to be a degraded product of the 24-kDa hHsp70 520-641. These findings confirmed the results of the previous study (19) demonstrating that the dimerization as well as the oligomerization of Hsp70 was mediated through the C-terminal client-binding domain. Moreover, the results in Fig.…”
Section: Dimerization Of the C-terminal Client-binding Domain -Polyacsupporting
confidence: 82%
“…Previous studies consistently showed that the C-terminal client-binding domain is responsible for the dimer/oligomer formation of Hsc70 (19). However, there was an apparent discrepancy as to the role of sub-domains, whether the client-binding sub-domain or the lid sub-domain is critical for this role.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, it seems inappropriate at this time to form rigid models of the priming step based on stoichiometry data that require the action of specifically a monomer or a dimer of hsp70 on the receptor. It is possible that only one molecule of hsp70 is bound directly to and interacting productively with the receptor, and that under these conditions of assembly with purified proteins the receptor-bound hsp70 can associate with other molecules of hsp70 to form dimers and trimers, much as purified hsp70 and its homologs have been shown to do in solution (32)(33)(34). It is perhaps important to note that analysis of both the native and assembled hsp90⅐Hop⅐hsp70 machinery has revealed a molar ratio of 1 hsp70 per hsp90 dimer (6,18).…”
Section: Fig 4 Release Of Primed Gr⅐hsp70 Complex and Visualizationmentioning
confidence: 99%
“…Bacterial DnaK and its mammalian mitochondrial and cytoplasmic homologs self-associate in solution into dimers, trimers, and probably higher oligomers, with the equilibrium between these forms being dependent upon the concentration of the chaperone and the equilibrium being shifted toward the monomer by ATP or binding of peptide substrate (32)(33)(34). Under concentrated conditions, our purified hsp70 is predominantly dimeric on native gel electrophoresis with some trimers being detectable, yet under dilute conditions in reticulocyte lysate, the free hsp70 behaves as a monomer on molecular sieve chromatography (6), as did our purified hsp70 (data not shown).…”
Section: Stoichiometry Of the Primed Gr⅐hsp70mentioning
confidence: 99%